The Effect of Bonus Compensation and Leverage on Earnings Management with Financial Performance as Intervening Variable - Prihastomo, Eka Deny; Khafid, Muhammad (Accounting Analysis Journal, 2018)
The purpose of this study was to analyze the effect of bonus compensation, and leverage to earnings management and financial performance as an intervening variable in the manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2014-2015. This study using method purposive sampling with 102 unit analysis of a population of 150 manufacturing companies. While the sample in this research there are 51 manufacturing companies. The analysis technique used in this research that Path Analysis. The analytical tool used was SPSS 21. The results showed that the bonus compensation significantly negative effect on earnings management. Leverage has no effect on earnings management and financial performance. Financial performance significantly has a positive effect on earnings management. Bonus compensation significantly has a positive effect on financial performance. The conclusions from the results of this study showed that the variable of financial performance positively and significantly is able to mediate the relationship between compensation bonuses to earnings management. However, the financial performance variables cannot mediate the relationship between leverage to earnings management.